2021
DOI: 10.3390/su13116158
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of the Environmental Corrosivity in Museums by RFID Sensors: Application to Pollution Emitted by Archeological Woods

Abstract: The control of air quality in museums or storages is of fundamental interest for the conservation of historic artifacts. The present work reports an example of application of RFID sensors developed in the European project SensMat and dedicated to this issue. The sensors are based on the variation of property of an RFID tag coupled with a sensitive silver thin film exposed to the environment. As it will be described in the paper, such low-cost sensors are interrogated by a commercial reader and provide the envi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…It is important to mention that in the aforementioned studies, real-time corrosion monitoring and corrosion rate calculation were not performed. However, Zhang et al [ 124 ], Zarifi et al [ 125 ], Deif et al [ 126 ], and Rioual et al [ 127 ] developed RFID-based low-cost corrosion monitoring systems with real-time update ability.…”
Section: Resultsmentioning
confidence: 99%
“…It is important to mention that in the aforementioned studies, real-time corrosion monitoring and corrosion rate calculation were not performed. However, Zhang et al [ 124 ], Zarifi et al [ 125 ], Deif et al [ 126 ], and Rioual et al [ 127 ] developed RFID-based low-cost corrosion monitoring systems with real-time update ability.…”
Section: Resultsmentioning
confidence: 99%
“…Its dimensions are 11.3 × 6.5 cm 2 . The principle of the sensor was described in detail elsewhere [26,27]. As shown, it is based on the electromagnetic coupling between a metallic sensitive thin film which acts as a coupon exposed to a corrosive environment and the antenna of an RFID tag.…”
Section: Principle and Selections Of Rfid Sensorsmentioning
confidence: 99%
“…A calibration procedure was performed in Ref. [27] to correlate the variation of RSSI measured by the RFID reader and the decrease of thickness of silver thin films. It was shown that by keeping a RSSI value of −45 dBm for the reference tag, the sensitive one is responding with a RSSI value of −55 dBm when a thickness of 7.5 nm of silver remains.…”
Section: Principle and Selections Of Rfid Sensorsmentioning
confidence: 99%
See 2 more Smart Citations